2020
DOI: 10.21315/tlsr2020.31.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Single Agent and Synergistic Activity of Maritoclax with ABT-263 in Nasopharyngeal Carcinoma (NPC) Cell Lines

Abstract: The BCL-2 anti-apoptotic proteins are over-expressed in many cancers and hence are attractive therapeutic targets. In this study, we tested the sensitivity of two Nasopharyngeal Carcinoma (NPC) cell lines HK1 and C666-1 to Maritoclax, which is reported to repress anti-apoptotic protein MCL-1 and BH3 mimetic ABT-263, which selectively inhibits anti-apoptotic proteins BCL-2, BCL-XL and BCL-w. We investigated the sensitisation of the NPC cell lines to these drugs using the SYBR Green I assay and 3D NPC spheroids… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Besides the anti-apoptotic function, BCL-2 and BCL-x L are emerged as master regulators of ER and mitochondrial dynamics in cancer cells [ 6 ]. Upregulation of the anti-apoptotic action of BCL-2 and BCL-x L was associated with apoptosis resistance of NPC cells [ 61 , 66 ]. It was therefore suggested that anti-NPC therapy can be achieved through disruption of PI3K−Akt-mediated oncogenic activities of BCL-2 and BCL-x L .…”
Section: Discussionmentioning
confidence: 99%
“…Besides the anti-apoptotic function, BCL-2 and BCL-x L are emerged as master regulators of ER and mitochondrial dynamics in cancer cells [ 6 ]. Upregulation of the anti-apoptotic action of BCL-2 and BCL-x L was associated with apoptosis resistance of NPC cells [ 61 , 66 ]. It was therefore suggested that anti-NPC therapy can be achieved through disruption of PI3K−Akt-mediated oncogenic activities of BCL-2 and BCL-x L .…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of BCL-XL for NPC cell survival was not interrogated in the same study. Our own study unveiled that co-inhibition of BCL-2 and BCL-XL did not induce cell killing in NPC [10]. This led to the re-evaluation of the utility of BCL-2 and BCL-XL as therapeutic targets in NPC.…”
Section: Introductionmentioning
confidence: 87%
“…Patients with negative BCL-2 expression were reported to display better disease free 5-year survival compared to patients with BCL-2 positive tumours [7]. There were number of studies which attempted to target the anti-apoptotic proteins for NPC treatment but the study ndings were unsatisfactory [8][9][10]. The problem lied largely on the failure to determine which anti-apoptotic proteins did NPC cells relied for survival.…”
Section: Introductionmentioning
confidence: 99%
“…The Dynamic BH3 profiling [3], the CRISPR/Cas9 genome editing technique [4] and BH3 mimetics given their selectivity in inhibiting the antiapoptotic proteins (an approach that is known as 'chemical parsing') [5] are approaches that can be used to parse the individual contributions of the BCL-2 anti-apoptotic proteins for cell survival. Our previous study showed that ABT-263, a small molecule inhibitor which selectively inhibits BCL-2, BCL-XL and BCL-w, had minimal effect on NPC cells, which made it clear that other anti-apoptotic proteins may be important for NPC cell survival [6].…”
Section: Introductionmentioning
confidence: 99%